Regulation of Dynamic Protein S-Acylation - Chen, Jessica J.; Fan, Ying; Boehning, Darren (Frontiers in Molecular Biosciences, 2021)
Protein S-acylation is the reversible addition of fatty acids to the cysteine residues of target proteins. It regulates multiple aspects of protein function, including the localization to membranes, intracellular trafficking, protein interactions, protein stability, and protein conformation. This process is regulated by palmitoyl acyltransferases that have the conserved amino acid sequence DHHC at their active site. Although they have conserved catalytic cores, DHHC enzymes vary in their protein substrate selection, lipid substrate preference, and regulatory mechanisms. Alterations in DHHC enzyme function are associated with many human diseases, including cancers and neurological conditions. The removal of fatty acids from acylated cysteine residues is catalyzed by acyl protein thioesterases. Notably, S-acylation is now known to be a highly dynamic process, and plays crucial roles in signaling transduction in various cell types. In this review, we will explore the recent findings on protein S-acylation, the enzymatic regulation of this process, and discuss examples of dynamic S-acylation.